Endoscopic Treatment of Extraforaminal Entrapment of L5 Nerve Root (Far Out Syndrome) by Unilateral Biportal Endoscopic Approach: Technical Report and Preliminary Clinical Results - Dong Hwa Heo; Sagar Sharma; Choon Keun Park (Neurospine, 2019)
Objective Far out syndrome is compression and entrapment of the L5 nerve root in the extraforaminal area between the hypertrophied L5 transverse process and the sacral ala. The purpose of this study was to describe the technique of unilateral biportal endoscopic decompression for far out syndrome and to analyze early clinical results after endoscopic decompression. Methods The authors consecutively performed operative treatments for 16 patients with unilateral extraforaminal entrapment of the L5 nerve root (far out syndrome) using percutaneous biportal endoscopies. We included only patients who were followed more than six months after surgery. Demographic characteristics, operative time, concomitant herniated disc, and surgical complications were investigated. Clinical outcomes were evaluated using modified MacNab criteria, the visual analogue scale (VAS) for legs, and the Oswestry Disability Index (ODI). Results Among 16 patients, a total of 14 cases with 4 males and 10 females were included in the study. The mean leg VAS and the ODI were significantly improved after unilateral biportal endoscopic surgery. Concomitant extraforaminal disc herniation was associated with a favorable outcome (p<0.05). Abdominal pain in the immediate postoperative period occurred in 2 patients. Abdominal pain was completely resolved with conservative management in both patients. Conclusion We were able to achieve successful decompression of unilateral extraforaminal entrapment of the L5 nerve root using unilateral biportal endoscopic surgery. A unilateral biportal endoscopic approach may be considered as an alternative surgical treatment for far out syndrome.